Acquired elastotic hemangioma, a little-known entity: report of a case with 15 years of evolution - Maria Claudia Alves Luce; Caroline Paias Ribeiro; Bethânia Cabral Cavalli Swiczar; Neusa Yuriko Sakai Valente (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Acquired elastotic hemangioma is a hemangioma variant first described in 2002. It is characterized by being a benign, solitary, slow-growing lesion, that appears in adulthood and is associated with solar exposure. It is a rare hemangioma variant with few cases reported in the literature. We present a case of acquired elastotic hemangioma on the back of the right hand and forearm in a male adult. Acquired elastotic hemangioma is a benign vascular proliferation associated with solar exposure, usually assymptomatic. It affects adults between 59 and 65 years of age. Histopatologically it is characterized by proliferation of small vessels in the upper dermis that are disposed parallel to the epidermis, and significant solar elastosis. The treatment is surgical, with no relapses reported.